The impact of regulatory changes on rating behaviour - Nodirbek Karimov; Alper Kara; Gareth Downing; David Marqués Ibá\~nez (European Central Bank (ECB), 2024)
We examine rating behaviour after the introduction of new regulations regarding Credit Rating Agencies (CRAs) in the European securitisation market. Employing a large sample of 12,469 ABS tranches issued between 1998 and 2018, we examine the information content of yield spreads of ABS at the issuance and compare the pre- and post-GFC periods. We find that the regulatory changes have been effective in tackling conflicts of interest between issuers and CRAs in securitisation. Rating catering seems to have disappeared in the post-GFC period. Yet we see limited effectiveness on rating shopping. It follows that rating over-reliance might be an issue, especially for investors of higher-quality ABS.
Keywords: G21; G28; 330; Securitisation; asset-backed securities; credit rating agencies; rating shopping; rating catering; rating inflation; Europe